Factors associated with depressive symptoms among chinese elderly in Kampung Baru Sungai Chua, Kajang, Malaysia - Choong, Horng Tatt (2015)
This cross-sectional study aimed to determine the association of socio-demographic,psychosocial, lifestyle, health, functional and nutritional factors with depressive symptoms (DS) among Chinese elderly. Respondents were recruited by convenience sampling method through house-to-house visit. Data were obtained through face-to-face interview using interviewer-administered questionnaire. Elderly Cognitive Assessment Questionnaire (ECAQ) was used to screen and exclude respondents with cognitive impairment. Geriatric Depression Scale (GDS) was used to assess DS. Social support, functional status, physical activity and dietary intake were assessed using Medical Outcomes Study-Social Support Survey (MOS-SSS), Barthel Index of Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL), Rapid Assessment of Physical Activity (RAPA) and 24-hour dietary recall, respectively. Weight, height, waist circumference, middle upper arm circumference, calf circumference were measured using standard procedures. The prevalence of DS among the respondents was 36.6%. Majority of the respondents were physically inactive (96.5%), received below-moderate social support (54.46±10.07), reporting abdominal obesity (61.6%), having at least one disease (84.8%) and taking medication (69.6%), and consuming excess selenium (81.9 ± 54.44 mcg) and inadequate calcium (309 ± 173.36 mg). Social support score (p<0.001) and number of pain symptom (p<0.001) were the predictors of GDS score. Folate (, p<0.01), magnesium (p<0.01) and iron (p<0.01) intake were significant predictor of GDS score only if confounding effect of dietary variables were ignored. After adjustment for gender, number of disease, current drinker,medication, functional dependent, and dietary folate and magnesium intakes, money satisfaction (OR=0.16, p<0.01), pain symptom (OR=0.25, p<0.05) and social support (OR=0.92, p<0.01) were significantly associated with risk reporting DS. This study suggested that folate, magnesium and iron play crucial roles in production of serotonin. To certain extent, these nutrients might reduce DS, but do not change the risk of reporting DS. DS could be improved through receiving frequent affection, and companionship from social environment, adequate money for living, being physically healthy and consuming foods rich in folate and magnesium, particularly among men.